Phycotoxins Dynamic from San-Pedro Port Area and their Potentials Associated Risks - Adon, Marie Paulette (European Journal of Applied Sciences, 2023)
The aim of this study was to study the phycotoxins variation from Container Terminal at the San-Pedro area (CTSP) and their potential associated risk. The methodology used consisted to collecte the phytoplankton of the remaining volume of sample taken using the Van Dorn bottle for the analysis of nutrient salts during June and July 2021 between 8 am and 3 pm in the differents stations from CTSP. Of 274 taxa collected in CTSP, a total of 20 phycotoxins was identified with a high diversity of the Dinophyta represented by 14 taxa and Cyanobacteria with 5 taxa. The first mission was characterized by a relatively number highest of Dinophyta taxa such as Prorocentrum lima and Prorocentrum micans, the last specie having observed in the majority of stations during the two sampling missions. During second mission, Cyanobacteria richness was high with a presence of Pseudanabaena catenata noted in all studies stations except the station S1 of site E. Except Pseudanabaena catenata which both syndrom and symptom were unidentified, eight syndroms such as Amnesic Shellfish Poisoning (ASP), Paralytic Shellfish Poisoning (PSP), Amyotrophic lateral sclerosis (ALS), Diarrheic Shellfish Poisoning (DSP), Ciguatera Fish Poisoning (CFP), Aerosol toxicity (AST), Clupeotoxism (CPT) and Neurologic Shellfish Poisoning (NSP) were individualised from phycotoxins identified. Due to the importance of the CTSP in the Ivorian economic and social activities, the interest of carrying out more in-depth studies would be necessary for the conservation of the biodiversity of this ecosystem, the presence of toxin-producing microorganisms could cause nuisances affecting all the links in the aquatic trophic chain and thus cause a serious threat to animals, human beings as well as aquatic plants than land irrigated with water contaminated by these toxins.